Some thoughts on R. J. Seddon and the emergence of New Zealand patterns of identitiy : thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Thom, Stuart (Massey University, 1973)
This thesis is a study of the way in which the colonists who sparsely populated the isolated colony of New Zealand during the latter half of the nineteenth century viewed themselves and the society which was developing around them. The colonists were predominantly of British origin and while their migration from Great Britain implied a partial rejection of British society, this was probably tempered by an enhanced loyalty to the British nation state. This loyalty was born of their realisation that the society they were creating was dependent upon its political, economic and military power. But Great Britain was a distant source of protection and the British authorities were often unresponsive to the demands of colonists made over-anxious by the apparent vulnerability of their colony to numerous threats. Fears arising from the isolation and the smallness of their community seem a constant undercurrent in the attitudes of the colonists towards themselves and the world. In the first instance therefore, the realisation of dependence upon Great Britain, and the colonists' British origins seem to have encouraged them to emphasise their Anglo-Saxon solidarity. They did this by their loyalty to the British nation state and by asserting their innate "racial" superiority to other ethnic groups who appeared to threaten them. These attitudes were probably strengthened by difficult communications within New Zealand. The colony was a land of forbidding relief and by 1870 there were only a few poorly constructed roads. Practically no railway track had been laid and coastal shipping, often the quickest and the most reliable means of transport, was still very slow and often haphazard in its operation.
Keywords: Richard John Seddon; Nationalism, New Zealand; National characteristics, New Zealand; Dick Seddon; New Zealand history